Viewpoints of Nigeria’s South-South Residents on Digital Communication, Transparency and Accountability in Governance in the Country - Jammy Seigha Guanah; Paul Bebenimibo (Polit Journal Scientific Journal of Politics, 2025)
This study investigated the perspectives of residents in Nigeria’s South-South region of Nigeria on the role of digital communication in promoting transparency and accountability in governance. The objectives of the research were threefold: to determine if digital communication is being utilised in the pursuit of transparency and accountability in governance in Nigeria; to assess the extent to which digital communication is being deployed in this pursuit; and to identify the challenges associated with digital communication in achieving transparency and accountability in governance in Nigeria. Using a quantitative approach, the study surveyed 385 residents in the South-South region. It made use of the Social Influence Theory (SIT) and the Technological Determinism Theory (TDT). The study found that digital communication is minimally employed in the quest for transparency and accountability in governance in Nigeria. The study also discovered that digital communication is being deployed in a low extent in the quest for transparency and accountability in governance in Nigeria. The findings further revealed that there are significant challenges hindering the effective use of digital communication in governance, including inadequate infrastructure, lack of digital literacy, and regulatory hurdles. It concluded that digital communication has the potential to enhance transparency and accountability in governance in Nigeria, but its effectiveness is contingent upon addressing the identified challenges. It was recommended that policymakers and stakeholders prioritise addressing these challenges to unlock the full potential of digital communication in promoting transparency and accountability in governance. Specifically, the study suggests that the government should invest in digital infrastructure, implement digital literacy programmes, and streamline regulatory processes to facilitate the effective use of digital communication in governance.